2011
DOI: 10.1016/j.physletb.2011.03.073
|View full text |Cite
|
Sign up to set email alerts
|

Generalised Tsallis statistics in electron–positron collisions

Abstract: The scaling of charged hadron fragmentation functions to the Tsallis distribution for the momentum fraction 0.01 x 0.2 is presented for various e + e − collision energies. A possible microcanonical generalisation of the Tsallis distribution is proposed, which gives good agreement with measured data up to x ≈ 1. The proposal is based on superstatistics and a Koba -Nielsen -Olesen (KNO) like scaling of multiplicity distributions in e + e − experiments.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 49 publications
4
84
0
4
Order By: Relevance
“…(43) has the form of a microcanonical distribution in the one dimensional case, D = 1. In [79,80] it was shown that smearing this distribution over a Gamma-type multiplicity distribution results in a microcanonical generalization of the Tsallis distribution which fits the fragmentation functions measured in e + e − experiments with similar q(s) evolution to that presented in fig. 2.…”
Section: Energy Fluctuations -Heat Capacitysupporting
confidence: 53%
“…(43) has the form of a microcanonical distribution in the one dimensional case, D = 1. In [79,80] it was shown that smearing this distribution over a Gamma-type multiplicity distribution results in a microcanonical generalization of the Tsallis distribution which fits the fragmentation functions measured in e + e − experiments with similar q(s) evolution to that presented in fig. 2.…”
Section: Energy Fluctuations -Heat Capacitysupporting
confidence: 53%
“…A respectable amount of papers applying this idea to one or the other area in physics appeared [14][15][16][17][18][19]. Since from this entropy the canonical energy distribution is power law tailed in place of the Boltzmann-Gibbs exponential, numerous high-energy distributions have been fitted using the Tsallis formula [12,[20][21][22][23][24][25][26][27][28]. Its independence from the thermostat and the thermodynamical foundation behind the use of such a formula are interesting questions.…”
Section: Motivationmentioning
confidence: 99%
“…We note that theoretically a really constant heat capacity, C 0 , stems from the equation of state eq. (22). The latter is a good ansatz for an effective equation of state of classical non-Abelian gauge field systems on the lattice [51] and represents the high-E limit of Planck's S (E) formula for thermal radiation.…”
Section: Applicationmentioning
confidence: 99%
“…In non-extensive statistics, the Tsallis parameter (q) is related to the temperature fluctuations [12] and therefore we estimate the speed of sound using Tsallis statistics in hadronic medium, and study it as a function of q, for systems undergoing small perturbations. Further, it has been observed that the transverse momentum spectra of the secondaries created in high energy p + p(p) [9,13,14,15,16,17,18,19], e + + e − collisions [20,21] are better described by the non-extensive Tsallis statistics [22]. In addition, non-extensive statistics with radial flow successfully describes the spectra at intermediate p T in heavy-ion collisions [23,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%